Oxygen uptake kinetics in children and adolescents: A review - Armstrong, N.; Barker, A. R. (Pediatric Exercise Science, 2009)
The pulmonary oxygen uptake (pVO2) kinetic response at the onset of exercise provides a noninvasive window into the metabolic activity of the muscle and a valuable means of increasing our understanding of developmental muscle metabolism. However, to date only limited research has been devoted to investigating the pVO2 kinetic response during exercise in children and adolescents. From the rigorous studies that have been conducted, both age- and sex-related differences have been identified. Specifically, children display a faster exponential rise in the phase II pVO2 kinetics, which are purported to reflect the rise in muscle O2 consumption, during moderate, heavy and very heavy intensity exercise compared with adults. Furthermore, for heavy and very heavy exercise, the O2 cost of exercise is higher for the exponential phase and the magnitude of the pVO2 slow component is smaller in young children. Sex-related differences have been identified during heavy, but not moderate exercise, with prepubertal boys displaying a faster exponential phase II pVO2 kinetic response and a smaller pVO2 slow component compared with prepubertal girls. The mechanisms underlying these differences are currently poorly understood, and form the basis for future research in this area. However, it is hypothesized that an age-related modulation of the muscle phosphate feedback controllers to signal an increased rate of oxidative phosphorylation and/or altered muscle fiber type recruitment strategies have the potential to play an important role. Overall, the data support the view that at the onset of exercise children have an enhanced potential for oxidative metabolism in the myocyte compared with adults.